Impact of Positive Emotion Regulation Training on Negative Symptoms and Social Functioning in Schizophrenia: A Field Test - Favrod, Jérôme; Nguyen, Alexandra; Tronche, Anne-Marie; Blanc, Olivier; Dubreucq, Julien; Chereau-Boudet, Isabelle; Capdevielle, Delphine; Llorca, Pierre Michel (Frontiers in Psychiatry, 2019)
Background: The poor efficacy of drug or psychological treatments on the primary negative symptoms of schizophrenia has led to the development of new interventions. The Positive Emotions Program for Schizophrenia (PEPS) is an emotion regulation strategy training that aims to intensify positive emotions and develop positive performance beliefs. A randomized controlled trial showed that PEPS is effective in reducing the composite score of the reduction of experience syndrome (anhedonia and apathy). The present study is designed to evaluate its feasibility in natural conditions to measure external validity of PEPS. Materials and Methods: Twenty-one participants recruited through the French national network of expert centers followed eight sessions of PEPS and were assessed pre- and posttest with the Scale for Assessment of Negative Symptoms (SANS) and the Personal and Social Performance (PSP). The scales of the SANS were divided into a composite score of the reduction of the ability to experience and a composite score of the reduction of expression. Results: All participants followed the 8 sessions of PEPS, and both composite scores were significantly and clinically improved at posttest. Social functioning assessed with the PSP was also improved. Conclusions: This field test shows that participation in PEPS is accompanied by a reduction of negative symptoms and an improvement of social functioning. Both negative syndromes, reduction of expression and reduction of experience, are improved. Participants are younger than those in previous studies, which may explain this unexpected result. However, this calls for a controlled study with younger participants.